Pendampingan Usaha Teh Rambut Jagung Desa Sragi Blitar sebagai Penciri Daerah yang Potensial di Masa Pandemi COVID-19 - Vritta Amroini Wahyudi; M. Zul Mazwan; Hanif Alamudin Manshur (STKIP Andi Matappa, 2021)
The purpose of community service is to provide production-packaging facilities for products, and providing marketing materials for corn silk herbal tea products on a micro-scale. The service is carried out offline (related to pandemic conditions) through stages 1) providing production and packaging facilities, 2) product regulation socialization, 3) product production and packaging training, 4) micro-scale marketing presentations. The service results include the availability of tea-making equipment, increasing the ability of the community to produce and package corn silk teabags, strategic understanding of micro scale marketing, and understanding the flow and requirements for submitting product regulations at the Health Office. Therefore, the service can operate sustainably with consistent production, regulatory requirements, and microscale sales practices as a superior regional product: corn silk antioxidant herbal tea.